Effects of l-Lysine on the physiochemical properties and sensory characteristics of salt-reduced reconstructed ham - Guo, Xiuxia; Tao, Shuo; Pan, Jinfeng; Lin, Xinping; Ji, Chaofan; Liang, Huipeng; Dong, Xiuping; Li, Shengjie (Meat science, 2020)
This paper aimed to investigate the dose-effects of l-Lysine (Lys, 0.2% to 0.8%) on the water holding capacity (WHC), textural properties, water mobility and distribution, microstructures and sensory acceptance of reconstructed ham with 50% reduction of added salt. Results showed that reducing salt from 2.50% to 1.25% caused significant increase in cooking loss and centrifuge loss, and decrease in hardness, springiness and chewiness. 0.8% Lys significantly improved the WHC and textural properties of salt-reduced hams, whereas 0.2% Lys further impaired these attributes. Moreover, 0.8% Lys improved the sensory scores for mouthfeel, appearance, taste and global acceptance. The NMR analysis reveals that water distribution and mobility were affected by salt reduction and Lys addition, and hams with 0.8% Lys contained more entrapped water with decreased mobility. Furthermore, a fine network with more bridge-linkage among myofibrils was formed in hams with 0.8% Lys. Therefore, addition of 0.8% Lys showed great potential in developing salt-reduced reconstructed ham with premium technological and sensory qualities.
Keywords: Animals; Sodium Chloride; Lysine; lysin; Cooking; barva; Meat Products; Salt-reduced; chlorid sodný; Water holding capacity; lidé; Myofibrils; prasata; Food Handling; Color; masné výrobky; voda; manipulace s potravinami; Water; Texture; Swine; Reconstructed ham; myofibrily; zvířata; vaření; Humans